2004
DOI: 10.1080/03009740310004351
|View full text |Cite
|
Sign up to set email alerts
|

Predominant inhibition of Th1 cytokines in New Zealand black/white F1 mice treated with FK506

Abstract: The T-helper 1/T-helper 2 (Th1/Th2) cell balance was examined in 6-month-old New Zealand black/white F1 (B/WF1) mice treated with an immunosuppressive agent, FK506. The survival rate of mice treated with 10 mg/kg/day of FK506 was 7/8, while that of those treated with 2.5 mg/kg/day was 5/8, and 4/8 after treatment for 8 weeks with placebo. Proteinuria, which was already positive in all mice before the treatment, in the seven of eight mice treated with 10 mg/kg/day remained mildly positive (< or = 1+), while sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
3
7
1
Order By: Relevance
“…6 This drug is known to affect the intestinal barrier, increasing permeability for allergenic food proteins, 2 and has been shown to induce a shift toward a T H 2 profile of cytokine and IgE production. 8,9 In our study increased total and specific IgE levels were observed in allergic patients but not in the control group, except in 1 control patient for total IgE. Tacrolimus-treated patients have an increased intestinal permeability and significantly higher serum LPS/endotoxin levels compared with healthy volunteers.…”
contrasting
confidence: 51%
“…6 This drug is known to affect the intestinal barrier, increasing permeability for allergenic food proteins, 2 and has been shown to induce a shift toward a T H 2 profile of cytokine and IgE production. 8,9 In our study increased total and specific IgE levels were observed in allergic patients but not in the control group, except in 1 control patient for total IgE. Tacrolimus-treated patients have an increased intestinal permeability and significantly higher serum LPS/endotoxin levels compared with healthy volunteers.…”
contrasting
confidence: 51%
“…Abs both to DNA and histone are believed to be important in the pathogenesis of SLE (Muller et al, 2008; Kiss et al, 2009; Cohen-Solal and Diamond, 2011; Pavlovic et al, 2011), and at least for pathogenic anti-DNA Abs there is a bias towards Abs of the IgG2a and IgG3 isotypes (Sugiyama et al, 2004; Baudino et al, 2006; Mannoor et al 2012; Moser et al, 2012). It is important to note that variations in binding between PL9-11 switch variants were not only related to C region differences, but also to the properties of the Ag studied.…”
Section: Discussionmentioning
confidence: 99%
“…1D). Cyclosporin A and FK506 inhibited both the Th1 and Th2 immune responses (49)(50)(51). Fusaruside showed a significant resolution of TNBS-induced colitis in mice by inhibiting IFN-g/STAT1/T-bet signaling (Fig.…”
Section: Discussionmentioning
confidence: 99%